Politics and jurisprudence of the Chaudhry court - Cheema, Moeen H. (ed.); Gilani, Ijaz Shafi (ed.) (New Delhi, 2015)
This volume represents an attempt to fill this gap by closely analysing the jurisprudence of the Supreme Court and reflects on the likely legacy of Chief Justice Iftikhar Muhammad Chaudhry's tenure.
Keywords: Political questions and judicial power